Drainage system analysis using Storm Water Management Model (SWMM) in flood mitigation efforts in the valley area - Asferizal, Ferial; Mashuri, Mashuri; Hasibuan, Hotmida R. (SINERGI, 2024)
This research takes place in the North Siantar Subdistrict of Pematangsiantar City, where issues with the drainage system result in frequent flooding in the valley area. Previously, this phenomenon has not been extensively researched. The study aims to analyze infiltration wells on Bah Tongguran Street in the North Siantar Subdistrict of Pematangsiantar City through existing drainage simulation using SWMM software. Water pooling at this location leads to floods due to insufficient drainage capacity, exacerbated by the valley-shaped land contour and high population density. The simulation results, utilizing SWMM software with the Gumbel method for rainfall distribution and a 5-year return period, revealed that the channels on both sides of Bah Tongguran Street cannot accommodate rainwater discharge. The dimensions of the existing drainage channel are b = 0.3 and h = 0.45. To address this issue, we propose the construction of infiltration wells with a diameter of 1.4 meters and a depth of 1.5 meters. The analysis determined that the infiltration wells would be 24 wells on the left and 21 on the right. These infiltration wells will be constructed using concrete pipes, with an effectiveness rate of 65% for the left side and 58% for the right. Through this intervention, our research aims to serve as a reference for planners designing infiltration wells in valley areas and as a resource for other researchers developing sustainable flood mitigation technologies.